1934
DOI: 10.1084/jem.60.5.581
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Mechanism of Invasiveness of Streptococci

Abstract: Opie (1) and have demonstrated that various materials are fixed in situ when injected into an acutely inflamed area, and Menkin has emphasized the r61e of mechanical obstruction in the form of a fibrinous network and thrombosed lymphatics in the fixation of such substances as bacteria and trypan blue as an important factor in the resistance of tissues to invasion. Recently, Menkirl (6) has ascribed the characteristic lack of invasiveness of Staphylococcus aureus to the irritating properties of that organism w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1935
1935
1942
1942

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…to other weapons of the invader, (leucocidin, fibrinolysins, ability to tolerate phagocytosis) and to the bactericidal power of the blood, prevention of formation of fibrin clot, etc. (194,99,15,248,104,47,245). The dermo-necrotizing effect shown by' practically all Staphylococcus aureus strains (195) as the most immediate proof of their local invasiveness seems specially interesting in this respect.…”
Section: Downloaded Frommentioning
confidence: 99%
“…to other weapons of the invader, (leucocidin, fibrinolysins, ability to tolerate phagocytosis) and to the bactericidal power of the blood, prevention of formation of fibrin clot, etc. (194,99,15,248,104,47,245). The dermo-necrotizing effect shown by' practically all Staphylococcus aureus strains (195) as the most immediate proof of their local invasiveness seems specially interesting in this respect.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The dye or bacteria injected intravenously could likewise be fixed at a site of inflammation. These findings were confirmed by Dennis and Berberian (54). The phenomenon suggests the action of staphylocoagulase (126), but Menkin and Walston reported that staphylocoagulase is unrelated to the substance which induces rapid obstruction of the flow of lymph (181).…”
Section: Mode Of Infection By Staphylococcimentioning
confidence: 75%
“…Assuming the lytic action of any strain on human fibrin to be associated with its invasive power, the majority of these strains are potential human pathogens. 9 …”
Section: Discussionmentioning
confidence: 99%
“…A number of strains isolated were subjected to tests to determine their fibrinolytic activity * against human fibrin, since studies by Tillett and Garner,8 Dennis and Berberian 9 and Tillett 10 indicate that this property is closely associated with the virulence or invasive power of a strain. Of 14 strains from 14 individuals so tested, 9 produced fibrinolysis in from 3 to 45 minutes; 2 required 1 to 4 hours; 3 were either negative or required 10 to 12 hours.…”
mentioning
confidence: 99%